1982
DOI: 10.1182/blood.v60.6.1247.1247
|View full text |Cite
|
Sign up to set email alerts
|

Changes in phosphatidylinositol-4,5-bisphosphate 10 seconds after stimulation of washed rabbit platelets with ADP

Abstract: Adenosine diphosphate (ADP) induced aggregation of rabbit platelets, without the release reaction, causes a significant decrease (7%) in the amount of phosphatidylinositol-4,5-bisphosphate (PIP2) at 10 sec and at 60 sec (11%). In platelets prelabeled with 32P-phosphate, this decrease in PIP2 is associated with a decrease in PIP2 radioactivity, which is significant at 50 sec. The decrease in PIP2 is sufficient to mobilize about 0.18 nmole Ca2+/10(9) platelets. In view of the key role played by Ca2+ in ADP-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(30 citation statements)
references
References 27 publications
6
24
0
Order By: Relevance
“…1 previous observations , the levels of P2Plphosphatidic acid increased markedly by 15s after TRH addition and that of [32P]PtdIns did not increase until after 2 min (results not shown). The rapid decreases in [32P]PtdIns(4,5)P2 and [32PlPtdIns4P in GH3 cells after TRH stimulation are similar to recent observations in rat hepatocytes stimulated by vasopressin Thomas et al, 1983) and in horse platelets stimulated by thrombin (Billah & Lapetina, 1982;Vickers et al, 1982). In cells labelled to isotopic steady-state with [32P1P , TRH caused a decrease in Ptdlns(4,5)P2 from 33 + 2.3 pmol/106 cells to 22+ 1.lpmol at 30s (P<0.01).…”
Section: Inositol Sugar Analysissupporting
confidence: 89%
“…1 previous observations , the levels of P2Plphosphatidic acid increased markedly by 15s after TRH addition and that of [32P]PtdIns did not increase until after 2 min (results not shown). The rapid decreases in [32P]PtdIns(4,5)P2 and [32PlPtdIns4P in GH3 cells after TRH stimulation are similar to recent observations in rat hepatocytes stimulated by vasopressin Thomas et al, 1983) and in horse platelets stimulated by thrombin (Billah & Lapetina, 1982;Vickers et al, 1982). In cells labelled to isotopic steady-state with [32P1P , TRH caused a decrease in Ptdlns(4,5)P2 from 33 + 2.3 pmol/106 cells to 22+ 1.lpmol at 30s (P<0.01).…”
Section: Inositol Sugar Analysissupporting
confidence: 89%
“…We have previously reported that stimulation of rabbit platelets with ADP caused a decrease in the chemical amount of PIP2, possibly due to reduced synthesis (Vickers et al, 1982. This decrease in PIP2 was accompanied by an increase in specific radioactivity of PIP2 in platelets labelled with [32P]phosphate and [3H]glycerol.…”
Section: Introductionmentioning
confidence: 92%
“…The silica gel containing the phospholipids was scraped into test tubes for digestion with HC104 prior to phosphate analysis (Chalvardjian & Rudnicki, 1970;Duck-Chong, 1979) and determination of radioactivity. The methods have been described in detail previously (Vickers et al, 1982).…”
Section: Fractionation Of Platelet Phospholipids and Determination Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 3 H]PC was detected by Radioscanner Isomess 3000 Radio‐TLC Analyzer (‘RITA’, Raytest) or PC mass was visualized by I 2 vapor. The PC spots were scraped, extracted from the silica [21] and aliquots taken for scintillation counting and PC mass determinations as P i with a malachite green method [22].…”
Section: Methodsmentioning
confidence: 99%